Flow pulses shape periphyton differently according to local light and nutrient conditions in experimental lowland streams - Calvo, Clementina; Pacheco, Juan Pablo; Aznarez, Celina; Jeppesen, Erik; Baattrup‐Pedersen, Annette; Meerhoff, Mariana (Freshwater biology, 2022)
Streams generally are affected by multiple stressors acting at different timescales. Periphyton, often the most important primary producer in these ecosystems, may respond to short‐term impacts as well as to different long‐term environmental conditions with potentially various changes in community structure. Here, we experimentally investigated the effects of sudden flow pulses on periphyton communities as a way to mimic extreme precipitation events in lowland streams that are predicted to occur more often with climate change in some regions. Using outdoor flumes, we allowed periphyton to colonise nutrient‐diffusion substrates under two light conditions (50% shade and fully open) and nutrient availabilities (control, with access only to stream nutrients, and N–P‐enriched) along a gradient in baseflows (0.43 to 2.17 L/s). After one month, we exposed the communities to a flow pulse (two‐fold peak flow increase to simulate conditions of a potentially high disturbance) and analysed the responses of biomass and taxonomic composition. Flow pulse promoted periphyton growth in the lowest range of the baseflow but led to biomass reduction in the highest range. Light was the second major driver of biomass accrual, whereas nutrient enrichment had a strong effect on community composition both before and after the pulse (i.e., diatom dominance vs. green algae dominance in scenarios without and with enrichment, respectively). In all treatments, the flow pulse promoted a higher taxonomic richness, suggesting a partial reset of the succession of the periphyton communities. However, independent of flow and resources, periphyton communities showed low ecological resistance against the pulse with changes in chlorophyll a, biovolume and taxonomic richness to the pulse. We demonstrated that the effects of pulses on periphyton are similar in terms of biomass but varied strongly regarding composition depending on their initial structure, which is in turn mediated by the baseflow normally experienced by the systems, and on light and nutrient availability. Our results highlight the importance of testing multiple stressors, such as an increase in extreme events, under a wide range of environmental conditions (i.e., flow regime, trophic state, light availability). This approach allows us to detect potential interaction effects and non‐linear responses, and highlights that the environmental settings ultimately determine the net effects of flow pulses on community structure and probably also on several important ecosystem processes.